Wheat - Gunnarsson, Astrid (2014)
Increasing volatility and less political intervention from the CAP in the market price of wheat is making it more difficult than in the past for Swedish farmers to determine the price at which they should sell their wheat. In the past, the Swedish farmer-owned company Lantmännen has traditionally set a guideline price for Swedish wheat every year to which farmers could adapt, but ceased doing so last year. Therefore this study sought to identify the parameters on which the price of wheat is dependent on by using a reduced form model. The perspective adopted was that of farmers. The model proved able to identify the main factors determining the annual price fluctuations in wheat, with all variables included having an impact on the wheat price, except export quantity in the previous year. The results is showed in percentage by using the elasticizes and are providing an understanding of the variables affecting the price of wheat, allowing farmers in Sweden to better understand the relative importance of the driving forces of wheat price changes.